Mathematics learning and teaching directed to process construction: reflection on the application of mathematical induction - Yaqiong Li; Wenbin Xu; Yiwen Xu; Bao Liu (Annals of Mathematical Modeling, 2022)
The Theory of Meaningful Learning shows that: to achieve the best learning effect, new knowledge should establish a non-arbitrary and substantial relationship with the existing knowledge in the learner’s cognitive structure, and the focus of the construction of the learning process is to combine the relationship between learning and teaching factors. Therefore, through the description of the application process of "Mathematics Induction", this article draws practical reflection: the process of mathematics learning requires learners to pay attention to real experience, independent thinking, and learning reflection, which inspires teachers to pay attention to in teaching: through creating appropriate problem situation and using appropriate teaching resources, they should pay attention to the time sequence of teaching, and guide students appropriately to take the initiative in discovering learning. In this process, students are guided to actively sort out, integrate and apply knowledge. Through a reasonable learning process experience, students can construct knowledge structure in an orderly manner, improve the quality of thinking, improve the ability to analyze and solve problems, and realize the pedagogical significance of subject teaching.